ADAPTASI PETANI SAWAH TERHADAP MODERNISASI TEKNOLOGI PERTANIAN DI GAMPONG BLANG ARA KEUDE KABUPATEN NAGAN RAYA - Rozatul Annisa; Maisyura Maisyura; Sherlia Darmayani; Aja Fitria; M. Luttan Irwanto Tarigan; Sopar Sopar; Riki Yulianda; Saiful Asra; Samwil Samwil (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
Rice farmers who have accepted the era of modernization easily adapt to technological sophistication because they tend to be faster and more precise. Technology in the form of environmentally friendly agricultural tools can increase farmer productivity so that they produce quality and abundant harvests in a short time. Although the development of agricultural technology often flaps its expansion, the increasingly rapid modernization of agriculture, farmers in Gampong Blang Ara Keude are in fact very easy to adapt to existing technology without having to socialize with the existence of technological modernization. The purpose of the researcher taking the title above is to develop farmers in Gampong Blang Ara Keude, Nagan Raya Regency. The results of this study indicate that farmers in Gampong Blang Ara Keude, Nagan Raya Regency are starting to get used to using technology in agricultural activities. Such as using organic fertilizers, tractors, reapers, milling machines, and others. However, for marketing, they still use traditional methods, namely by distributing them to the nearest staple food agent outlets. In fact, even though rice farmers in Gampong Blang Ara Keude easily accept technological modernization, not all harvests necessarily bring maximum results. They even said that this crop failure was a disaster from Allah SWT, the Almighty God, because the local residents were not grateful enough to the Creator.